2014
DOI: 10.1042/cs20130618
|View full text |Cite
|
Sign up to set email alerts
|

Physical ischaemia induced by isometric exercise facilitated collateral development in the remote ischaemic myocardium of humans

Abstract: The aim of the present study was to investigate the effects of isometric-handgrip-induced PIT (physical ischaemia training) on remote coronary recruitment and growth. A total of 74 CAD (coronary artery disease) patients were randomly assigned to either the IHG (isometric handgrip group) or NEG (non-exercise group). Patients in the IHG performed isometric handgrip exercises during 1 min of coronary balloon occlusion, whereas patients in the NEG remained sedentary. CFI (collateral flow index), HR (heart rate), S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Previous study conducted by our research team showed that PIT can increase the expression of VEGF, thereby resulting in accelerating revascularization and coronary blood flow recovery (8). Lin et al also reported that isometric handgrip-induced PIT could increase the expression of VEGF and the coronary collateral flow in patients with coronary heart disease; the increased VEGF may in turn contribute to collateral angiogenesis in the remote ischemia heart region (9). Sandri et al observed elevated VEGF level after a 15-min suprasystolic occlusion of one lower extremity in healthy volunteers (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study conducted by our research team showed that PIT can increase the expression of VEGF, thereby resulting in accelerating revascularization and coronary blood flow recovery (8). Lin et al also reported that isometric handgrip-induced PIT could increase the expression of VEGF and the coronary collateral flow in patients with coronary heart disease; the increased VEGF may in turn contribute to collateral angiogenesis in the remote ischemia heart region (9). Sandri et al observed elevated VEGF level after a 15-min suprasystolic occlusion of one lower extremity in healthy volunteers (18).…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al tested isometric handgrip exercise-induced PIT in 74 patients with coronary artery disease and found that the myocardial perfusion and left ventricular ejection fraction were significantly improved in PIT group. They concluded that PIT may promote remote collateral recruitment and growth (9). To the best of our knowledge, however, the effectiveness and mechanisms of PIT on patients with stroke have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden occlusion of a major coronary artery can result in AMI and rapid apoptosis of cardiomyocytes, leading to progressive fibrous replacement in the myocardium and LV dilatation [3,25]. Previous studies [26][27][28] demonstrated that physiologic RIT could promote coronary collateral formation in the ischemic myocardium. Results of capillary density and VEGF protein level in this study also demonstrated it.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature using maximal grip intensity exercise for at-home training has included heterogeneous and inconsistent HG protocols with work–rest timing cycles of 1:1 second, 14 10:20 seconds, 15 40 grips/min, 15 and 1:1 minute, 13 and total exercise durations of 30 minutes, 14 10 minutes, 15 and 40 minutes. 13 None of the previous research has experimentally quantified actual grip performance in reference to the prescribed maximal intensity, an important consideration when evaluating the acute CV responses.…”
Section: Part 1: the Mint Exercise Protocolmentioning
confidence: 99%
“…Protocols using maximal grip force against generic grip objects have successfully induced positive CV adaptations such as collateral vascular recruitment and growth, 13 reduced BP and improved local blood flow, 14 and reduced ergoreflex activity. 15 Despite these positive impacts on CV health indices, recommendation of this accessible exercise option by health care providers and exercise professionals is rare.…”
Section: Introductionmentioning
confidence: 99%